An identity-based motivational model of the effects of perceived discrimination on health-related behaviors. (July 2016) - Smart Richman, Laura; Blodorn, Alison; Major, Brenda
Perceived discrimination is associated with increased engagement in unhealthy behaviors. We propose an identity-based pathway to explain this link. Drawing on an identity-based motivation model of health behaviors (Oyserman, Fryberg, & Yoder, 2007), we propose that perceptions of discrimination lead individuals to engage in ingroup-prototypical behaviors in the service of validating their identity and creating a sense of ingroup belonging. To the extent that people perceive unhealthy behaviors as ingroup-prototypical, perceived discrimination may thus increase motivation to engage in unhealthy behaviors. We describe our theoretical model and two studies that demonstrate initial support for some paths in this model. In Study 1, African American participants who reflected on racial discrimination were more likely to endorse unhealthy ingroup-prototypical behavior as self-characteristic than those who reflected on a neutral event. In Study 2, among African American participants who perceived unhealthy behaviors to be ingroup-prototypical, discrimination predicted greater endorsement of unhealthy behaviors as self-characteristic as compared to a control condition. These effects held both with and without controlling for body mass index (BMI) and income. Broader implications of this model for how discrimination adversely affects health-related decisions are discussed.